2015
DOI: 10.1136/neurintsurg-2015-011686
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional printing of anatomically accurate, patient specific intracranial aneurysm models

Abstract: ObjectiveTo develop and validate a method for creating realistic, patient specific replicas of cerebral aneurysms by means of fused deposition modeling.MethodsThe luminal boundaries of 10 cerebral aneurysms, together with adjacent proximal and distal sections of the parent artery, were segmented based on DSA images, and corresponding virtual three-dimensional (3D) surface reconstructions were created. From these, polylactic acid and MakerBot Flexible Filament replicas of each aneurysm were created by means of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 28 publications
0
69
0
1
Order By: Relevance
“…[279111419333637] One study in particular performed a more comprehensive evaluation across 22 patients with unruptured aneurysms, comparing the reproducibility of the length and thickness of the main arteries and the size of the aneurysm between a 3D-CTA and the printed model. [11] In all studies comprising both qualitative and quantitative assessments, significant differences between preoperative imaging and printed models were only observed in a few minute areas, indicating that these models accurately represent patient anatomy.…”
Section: Resultsmentioning
confidence: 99%
“…[279111419333637] One study in particular performed a more comprehensive evaluation across 22 patients with unruptured aneurysms, comparing the reproducibility of the length and thickness of the main arteries and the size of the aneurysm between a 3D-CTA and the printed model. [11] In all studies comprising both qualitative and quantitative assessments, significant differences between preoperative imaging and printed models were only observed in a few minute areas, indicating that these models accurately represent patient anatomy.…”
Section: Resultsmentioning
confidence: 99%
“…The fabrication of aneurysm replicas has been described elsewhere [13]. Briefly, digital surface models were created retrospectively from segmented 3D digital subtraction angiography images that were acquired during clinical diagnosis.…”
Section: A Aneurysm Replicas and Experimental Setupmentioning
confidence: 99%
“…The method can be carried out in 2D (single slice), 3D (multiple slices), or 4D (multiple slices + time), where the fourth dimension is time and flow is visualized at different phases in the cardiac cycle. Previous work has shown that pcMRI can be carried out in anatomically accurate, 3D printed aneurysm replicas [12][13]. Herein we present comparisons between the hemodynamics before and after placement of a flow diverter in aneurysm replicas (n=3).…”
Section: Introductionmentioning
confidence: 96%
“…Some newly developed multimaterial 3D printers can produce models with multiple tissue types. As a result, some of the models produced by rapid prototyping are able to replicate actual patients' anatomical structures with remarkable realism (37,(54)(55)(56)(57).…”
Section: D Rapid Prototypingmentioning
confidence: 99%
“…One study found a strong correlation between 3D-printed models and the actual patients' anatomy (57). Additionally, studies have shown that surgeons using these models find them easy to use and superior to the use of traditional imaging alone (54,58).…”
Section: D Rapid Prototypingmentioning
confidence: 99%